2021
DOI: 10.46827/ejoe.v6i1.3543
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Social Situations Relational Phenomena in Young Children: A Review of Recent Evidence

Abstract: This literature review studies the recent research conducted in many countries. The purpose of this article is to review the recent literature regarding the ways children aged 3 to 5 understand and interpret social situations and if socialization is important at this age. This question is at the heart of the present research, especially in a COVID-19 era that still keeps children in their home without any interaction with their peers. The search strategy resulted in total of 24 articles that were selected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Thus, homework and other learning activities completed away from the school environment help them to achieve better grades. The more the parents interact with their children's learning activities in their early childhood years, the better the children get in literacy and mathematics [76]. This conclusion is in accordance with the results found in Bosede, and Abiodun, [77] study where it was shown that there is a significant correlation between home and school environmental factors and children's cumulative learning, especially in primary schools.…”
Section: Necessity and Possibility Of Educating "Charismatic" Studentssupporting
confidence: 90%
“…Thus, homework and other learning activities completed away from the school environment help them to achieve better grades. The more the parents interact with their children's learning activities in their early childhood years, the better the children get in literacy and mathematics [76]. This conclusion is in accordance with the results found in Bosede, and Abiodun, [77] study where it was shown that there is a significant correlation between home and school environmental factors and children's cumulative learning, especially in primary schools.…”
Section: Necessity and Possibility Of Educating "Charismatic" Studentssupporting
confidence: 90%
“…This means that people focus on a spiritual level and cultural improvement. For this reason, the environment of each child is very important for the socialization that each child will receive (Gregoriadis et al, 2020;Aslanidou, 2019;Aslanidou, 2021). Beka-Bajrami (2022) states that the development of picture books based on information technology has a broad development prospect.…”
Section: Theoretical Background a It In Educationmentioning
confidence: 99%
“…Acting on this recommendation could produce substantive empirical findings that highlight why special education teachers express turnover intentions within their first five years of employment (Millett Scallon et al, 2023;Newton, 2018;Newton et al, 2022). Concurrently, the recommendation offered here suggests that professional development programs must reflect individual differences in professional competencies and extend to the broader community (Aslanidou, 2019;Dennison et al, 2020;Gann & Carpenter, 2018Holmqvist & Lelinge, 2021;Kaniamattan & Oxley, 2022;Kunzman & Gaither, 2020;Lopes & Oliveira, 2021). As these programs emphasize that leaders must possess exceptional skills, they also warrant discussions of which theoretical constructs must apply.…”
Section: Concluding Need For Further Researchmentioning
confidence: 87%